Gambaran Kecemasan Lansia Akan Vaksinasi Covid-19 di Wilayah Kerja UPTD Puskesmas Tajuncu Kabupaten Soppeng 2022 - Nurhardianti; Anggeraeni; Wirasni (Yayasan Literasi Sains Indonesia, 2022)
The Covid-19 pandemic brings new challenges to the country. In particular, how countries are responding and working to contain and prevent the further spread of the virus. The Covid-19 vaccination is one solution in an effort to break the chain of the spread of Covid-19. The implementation of the Covid-19 vaccination that occurred in the elderly caused anxiety which certainly hampered the vaccination process. The purpose of this study was to find out the description of the elderly's anxiety about Covid-19 vaccination in the UPTD Tajuncu Health Center working area. This research is a descriptive study with a qualitative approach. The method of collecting this case study is interviews, observations, and questionnaires. This case study was conducted on June 2022 in the UPTD Tajuncu Health Center, Soppeng Regency. Based on the results of the case studies that have been carried out, 86 clientis experiencing moderate anxiety when he is going to carry out the Covid-19 vaccine, it is hoped that in the future the community will not feel anxious anymore to carry out the Covid-19 vaccine so that it can overcome the pandemic. It is hoped that the community will continue to apply health protocols, wash hands, wear masks, keep a distance, stay away from crowds and reduce mobility for the prevention of Covid-19.